2000
DOI: 10.1093/jnci/92.23.1918
|View full text |Cite
|
Sign up to set email alerts
|

Her-2-neu Expression and Progression Toward Androgen Independence in Human Prostate Cancer

Abstract: Her-2-neu expression appears to increase with progression to androgen independence. Thus, therapeutic targeting of this tyrosine kinase in prostate cancer may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
239
1
6

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(264 citation statements)
references
References 46 publications
18
239
1
6
Order By: Relevance
“…Furthermore, in prostate cancer cell lines, we found that androgen-sensitive LNCaP cells and castration-resistant C4-2 cells also overexpressed this protein (Figure 3). Our findings are consistent with the majority of patient-related reports in literature, [5][6][7][8]10,11 as well as some in vitro and animal model studies. 13,48,49 Furthermore, it has been recently reported that in men with long-term follow-up after HER-2 targeting of prostate cancer K-x Zhang et al radical prostatectomy, HER-2 expression when combined with percentage DNA index can be used clinically for prediction of progression, metastasis and prostate cancerspecific death.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, in prostate cancer cell lines, we found that androgen-sensitive LNCaP cells and castration-resistant C4-2 cells also overexpressed this protein (Figure 3). Our findings are consistent with the majority of patient-related reports in literature, [5][6][7][8]10,11 as well as some in vitro and animal model studies. 13,48,49 Furthermore, it has been recently reported that in men with long-term follow-up after HER-2 targeting of prostate cancer K-x Zhang et al radical prostatectomy, HER-2 expression when combined with percentage DNA index can be used clinically for prediction of progression, metastasis and prostate cancerspecific death.…”
Section: Discussionsupporting
confidence: 93%
“…In prostate cancers, overexpression of HER-2 has been reported to be associated with progression to androgen independence, [5][6][7][8]10,11 although some contradictory results have also been reported. 39,40 To normalize variables such as fixation and staining procedures, which could account for the reported differences, we used a TMA approach where 105 unique prostate tissue cores from 35 patients were immunostained for HER-2 simultaneously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, EGF or heregulin had no effect on promoting the adhesive ability of C-33 cells (Supplementary Figure 4). We propose that in androgenindependent, AR-positive PCa cells, ErbB-2 protein is constitutively activated and/or elevated as seen in clinical samples due, in part, to the loss or null of cPAcP expression (Signoretti et al, 2000;Veeramani et al, 2005). In those advanced PCa cells, signal pathways initiated by highly activated ErbB-2 lead to a sustained activation of PYK2 and PYK2-mediated functions, which differs from the transient effect activated by ErbB ligands (Zrihan-Licht et al, 2000;van der Horst et al, 2005;Park et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…In most prostate epithelia, only three members of this family, but not ErbB-4, are expressed (Robinson et al, 1996). In prostate carcinomas, the erbB-2 gene is not amplified and its protein level is elevated in some advanced tumors during androgen ablation therapy (Signoretti et al, 2000). In androgen-independent human PCa cells, ErbB-2 is greatly activated by tyrosyl phosphorylation, at least in part due to the low or null expression of cellular prostatic acid phosphatase (cPAcP), a prostate-unique tyrosine phosphatase that dephosphorylates ErbB-2 .…”
Section: Introductionmentioning
confidence: 99%